Virgin coconut oil: emerging functional food oil - Abdul Manaf, Marina; Che Man, Yaakob; Ismail, Amin (Elsevier, 2009)
Virgin coconut oil (VCO) is growing in popularity as functional food oil and the public awareness of it is increasing. It is expected that VCO will experience a dramatic growth in the market. The introduction of VCO has open up new research that basically reveals new things besides what has already been known on commercial coconut oil. This paper mainly discusses on some of the findings associated with VCO up to date. Physicochemical properties, antioxidant activity, clinical and authentication studies of VCO were some of the topics addressed in this review.